Effects of Magnetic Field in Creep Behavior of Three-Phase Laminated Composite Cylindrical Shells - Komeil Hosseinpour; Ahmad Reza Ghasemi (Mechanics of Advanced Composite Structures)
Due to the importance effect of magnetic field on the history of long-term radial and circumfer-ential creep strain and radial displacement for a three-phase nano-composite exposed to an internal pressure and placed uniform temperature, the present article subject has been pro-posed. Three-phase nano-composite made of single-walled carbon nano tubes (SWCNTs)/ glass fiber (GF)/vinylester used to micromechanical models in order to calculate the mechanical and thermal properties. By assuming non-linear viscoelastic based on Schapery integral model and using classical laminate theory, Prandtl-Reuss relations and Mendelson’s approximation meth-od achieved results. Distribution of the radial creep strain, circumferential creep strain and radial displacement in two states including without and with magnetic field and three tempera-ture conditions for laminated lay-ups [0/45/0/45] described for 10 years. The results indicate that the magnetic field has reduced the radial and circumferential creep strain and radial dis-placement. Furthermore, the temperature increase in the magnetic field is less effective on the increased values of creep strain and radial displacement. Finally, It has been founded that mag-netic field would reduce the creep strain of all case studies.